Reassessing the Building Construction System and Quality Issues in Relocated Settlement after the Gorkha Earthquake - Adhikari, Rabindra (Advances in Engineering and Technology: An International Journal, 2022)
This paper assesses the reconstruction process in a mountainous village that typically represents the dominant location of damage by the Gorkha earthquake of April 25, 2015. The pre- and post-earthquake scenarios are presented comparatively. The structural system is found to be mostly compliant as per the new guidelines set by the government; however, deficiencies in terms of construction system and structural characteristics were significant in the reconstruction. Thus, the reconstructed buildings with several deficiencies could be still seismically vulnerable. It is recommended that the performance of reconstructed buildings after the Gorkha earthquake shall be re-assessed for necessary risk management planning. Also, this study provides insight into the construction practice in after earthquake reconstruction and areas of poor workmanships in such work.